Revision of Heterococcopsis Borchsenius (Hemiptera: Coccoidea: Pseudococcidae), with description of a new genus with two new species from Turkey - Kaydan, M. Bora (Zootaxa, 2011)
The genus Heterococcopsis Borchsenius is revised. Heterococcopsis opertus Borchsenius is transferred to a new genus Heterobrevennia Kaydan gen. nov. and the adult females of two new species belonging to Heterobrevinnia are described: H. gullanae Kaydan spec. nov. and H. kozari Kaydan spec. nov. Heterococcopsis desertus Bazarov & Nurmamatov is transferred to the genus Phenacoccus Cockerell.